Optimalisasi Layanan Kesehatan, Gizi, dan Perawatan dalam Program Pengembangan Anak Usia Dini Holistik Integratif: Studi Kasus di TK Roselana Pecangaan, Kabupaten Jepara - Lestari, Sri; Rochmawati, Nur Intan (Jurnal Inovasi Pembelajaran di Sekolah, 2025)
The purpose of this study is to analyze the optimization of health, nutrition, and care services in the integrative holistic early childhood development program (PAUD HI), and to analyze the supporting factors of health, nutrition, and care services in the PAUD HI program at Roselana Kindergarten. The AUD HI program includes 5 essential needs of children that must be met, namely education services, health services, nutrition, and care, childcare services, protection services and welfare services. This study uses a qualitative descriptive research method, located in Roselana Kindergarten. Observation, interview, and documentation data collection techniques. Informants as a source of data in the research of school principals and teachers. The data analysis technique uses triangulation through the stages of data collection, data reduction, data presentation, and conclusion drawn. The results of this study show that nutritional health services and early childhood care get good health services by measuring weight, height, and head circumference in a programmatic and planned period. Children's health conditions can be monitored by a doctor's examination program every 2 months according to the child's needs, PMTAS every 1 week nutritious and non-MSG food, and treatment with PHBS. The partnership is established with the health center and the Jepara Regency Hospital. The conclusion of this study is that health, nutrition, and care services are one of the fulfillment of the essential needs of children in the PAUD HI program implemented optimally at Roselana Pecangaan Kindergarten in accordance with the indicators contained in Presidential Regulation Number 60 of 2023 concerning Integrative Holistic.